The Effect of Peanut Flour Substitution on the Organoleptic, Physical, and Chemical Characteristics of Sponge Cake - Lutfia Sri Saryo Saputri; Octavianti Paramitha (Universitas Negeri Padang, 2025)
This study aims to analyze the effect of peanut flour substitution on the organoleptic, physical, and chemical characteristics of sponge cake. An experimental method was employed using two formulations: F0 as the control (100% wheat flour) and F1 as the substitution formulation (50% peanut flour). Organoleptic evaluation was conducted by three expert panelists using a 1–9 rating scale, hedonic testing by 80 semi-trained panelists using a 1–9 hedonic scale, physical analysis using RGB histogram analysis in Adobe Photoshop, and chemical analysis covering moisture content, fat content, and protein content based on the AOAC method. The results showed that peanut flour substitution had no significant effect on organoleptic properties including aroma (p = 0.768), texture (p = 0.093), and taste (p = 0.116). In the hedonic test, all parameters including color (p = 0.458), texture (p = 0.878), taste (p = 0.954), and overall acceptance (p = 0.540) showed no significant difference between formulations, except for the aroma parameter (p = 0.001), where F1 was rated significantly more preferable than F0. Physical analysis indicated that F1 had a higher color brightness (mean RGB = 236.76) compared to F0 (mean RGB = 226.41). Chemically, F1 exhibited lower moisture content (43.62 ± 1.08%), higher fat content (17.77 ± 0.70%), and consistently high protein content (17.29 ± 3.23%). Peanut flour demonstrates potential as a partial substitute for wheat flour that enhances the nutritional value of sponge cake without significantly reducing sensory acceptance.